Menganalisis Penggunaan Teknologi AI dalam Personalisasi Pengalaman Customer - Yunda Syafira; Andini Kartika Dewi; Berliana Kristiana N.S; Norazlina Norazlina; Nosperiani Halawa; Sri Susanti (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The development of digital technology, especially Artificial Intelligence (AI), has significantly transformed the business and customer service landscape in the Industry 4.0 era. This study aims to analyze the application of AI technology in customer experience personalization and its impact on customer loyalty and satisfaction. This research employs a qualitative method with a literature review as the primary technique. The data used is secondary, sourced from credible references such as Google Scholar and peer-reviewed journals. The findings show that AI, through machine learning and Natural Language Processing (NLP), enables companies to understand and tailor services to individual customer preferences. Machine learning algorithms allow for the collection and analysis of customer behavior data to provide more accurate and relevant recommendations, increasing sales conversion and customer loyalty. NLP supports more natural customer interactions through chatbots and virtual assistants, enhancing responsiveness and service quality. However, challenges such as data privacy, information security, and algorithmic bias remain key obstacles in AI implementation. To address these issues, companies are advised to comply with data protection regulations such as GDPR and ensure transparency in AI-driven decision-making. In conclusion, the application of AI in customer experience personalization provides a competitive advantage for companies by improving operational efficiency, customer satisfaction, and loyalty, but it must be balanced with strict privacy and security policies.